Judges and Social Networks - Rosales, Carlos Manuel; Vargas, Oscar Ruiz (Frontiers in Law, 2024)
It is essential that the judicial function be public, discreet, and professional. Its legitimacy as a public authority is acquired through the recognition of judgments, in which there is an identification between decisions and society. But what type of communication must be made by the judiciary, and especially by judges, to provide information about their activities, and ensure that their interaction strengthens the republic, generating proximity between the sovereign and the public power.